1994
DOI: 10.1038/hdy.1994.152
|View full text |Cite
|
Sign up to set email alerts
|

Geographical cline in breeding systems and ploidy levels in European populations of Daphnia pulex

Abstract: Ninety populations of Daphnia pulex from sites throughout the UK and Scandinavia were assayed for genetic variation at 11 variable enzyme loci. A latitudinally-related dine in both breeding system and ploidy level was observed. Southern populations (latitudes 52-59°N) comprised only diploid cyclic parthenogens. Northern populations (latitudes 68-71°N) were dominated by polyploid obligate parthenogens and diploid cyclic parthenogens were absent. An assemblage of populations from a site of intermediate latitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 21 publications
4
58
0
Order By: Relevance
“…& Hebert, 1993). On the other hand, D. pulex exhibited a consistent south to north shift from sexual populations in the United Kingdom to asexual populations in northern Sweden (Ward et al, 1994). This shift, however, was accompanied by a change in ploidy : diploid in the south and polyploid in the north.…”
Section: (I) Plasticity and Patterns Of En Ironmental Ariation : Goalmentioning
confidence: 94%
“…& Hebert, 1993). On the other hand, D. pulex exhibited a consistent south to north shift from sexual populations in the United Kingdom to asexual populations in northern Sweden (Ward et al, 1994). This shift, however, was accompanied by a change in ploidy : diploid in the south and polyploid in the north.…”
Section: (I) Plasticity and Patterns Of En Ironmental Ariation : Goalmentioning
confidence: 94%
“…Clonal diversity in D. tenebrosa appears higher than that in other taxa of the pulex complex at the same site, with an average of 2.9 clones per pond compared with 1.7 clones for D. pulex and 1.5 for D. middendorffiana (Weider & Hebert, 1987a;Wilson & Hebert, 1992). Recent studies (Hobaek et al, 1993;Ward et al, 1994) have shown that populations of D. pulex from Eurasia have a similarly low level of clonal diversity (1.5 and 1.7 clones per pond). Higher clonal diversity estimates have however been reported for D. middendorffiana from a high-arctic site (4.5 clones per pond) and for D. pulex from a temperate zone region (2-4 clones per pond) (Hebert & Crease, 1983; (Weider & Hebert, 1987a;Zhao & King, 1989;Browne, 1992;Wilson & Hebert, 1992).…”
Section: Mtdna Analysismentioning
confidence: 99%
“…Arctic populations have completely abandoned sexual reproduction and include numerous polyploid clones (Beaton & Hebert 1988;Ward et a!., 1994). Allozyme analyses have shown that clonal diversity is very high in these obligate parthenogens with thousands of clones occurring over the species distribution.…”
mentioning
confidence: 99%
“…The accumulation of genetic data has showed that North American and European D. pulex are genetically two distinct species and nomenclature of the D. pulex complex is not resolved (Colbourne et al, 1998;Palsoon, 2000;Mergeay et al, 2006;Petrusek et al, 2008;Crease et al, 2012;Markova et al, 2013). Even in Europe, asexual strains of D. pulex show a more northerly distribution than sexual ones (Ward et al, 1994;Weider and Hobaek, 1997) and both lineages may co-exist within the same geographical region (Letho and Haag, 2010). In freshwater rock pools on islands of the Baltic sea archipelago (Southern Finland), the asexual strains belong to the North American clade whereas the sexual strains belong to the European clade (Letho and Haag, 2010).…”
Section: Introductionmentioning
confidence: 99%